РАЗВИТИЕ ТВОРЧЕСКОЙ ИНДИВИДУАЛЬНОСТИ ДЕТЕЙ И ПОДРОСТКОВ ЧЕРЕЗ ДЕКОРАТИВНОЕ И ИЗОБРАЗИТЕЛЬНОЕ ИСКУССТВО В ФОРМАТЕ КЛУБНОЙ РАБОТЫ БИБЛИОТЕКИ - КОВАЛЕНКО, заведующая читальным залом Филиала им. Л. Украинки, Виктория (BIBLIOPOLIS, 2020)
The creativity is a realization of individuality, a form of personal fulfillment; is a possibility to express the special and unique attitude to the world. The creativity and the self-expression is inherent to the human nature. The child like an adult tries to express its personality. However, not all of them can find the way of creativity and a lot of them cannot keep the creative skills for a long time. In that, they have a support of teachers, and in some ways, of librarians. The creative workshop for teens and young adults of the L. Ukrainka Branch is a good example. The article is about the implication of children in the theater and gaming activity, fine arts, crafts and decorative works in the club Kobzarik. The participation of teens in the club activity offers the opportunity to understand their interests. The widespread use of various types of aesthetic activity contributes to the awakening of artistic interests, the development of artistic imagination, artistic and creative abilities of students, and promotion of various art forms.